Dilemma during ultrasound‐guided internal jugular venous catheterization. Issue 10 (5th September 2017) - Dwarakanath, Sanjay; Cheriyan, Monica; Rebel, Annette
Key Clinical Message: The presence of Internal Jugular Valves can pose a diagnostic and procedural challenge during ultrasound‐guided cannulation. After ruling out dissection, thrombus, or ultrasound artifacts, it can still be accessed and successfully cannulated with appropriate precautions including use of Live ultrasound, positioning, use of soft‐tipped catheters, and minimizing duration of catheter placement. Abstract : The presence of Internal Jugular Valves can pose a diagnostic and procedural challenge during ultrasound‐guided cannulation. After ruling out dissection, thrombus, or ultrasound artifacts, it can still be accessed and successfully cannulated with appropriate precautions including use of Live ultrasound, positioning, use of soft‐tipped catheters, and minimizing duration of catheter placement.